PROTECTION AND MANAGEMENT OF PEAT ECOSYSTEMS FOR FOREST AND LAND FIRE PREVENTION IN WEST KALIMANTAN - Ahmad, Ahmad Khairul Fajri; Jitu Manangan, Rio; Elok Juwita, Nanda; Fide Armanda, Reyden (DE'RECHTSSTAAT, 2023)
Abstract: Environmental law plays an important role in the protection and management of peat ecosystems. The Peat Ecosystem has a very important function to prevent climate change, natural disasters, and to support the community's economy. The impact of peat damage that is of most concern is that it can cause forest and land fires (karhutla), including in West Kalimantan itself, which in particular has become an annual routine for forest and land fires (karhutla), especially in the summer. This makes researchers interested in examining what factors cause forest and land fires to occur, whether natural factors or human factors occur. This study uses a sociological juridical approach. The data collected in this study is secondary data through data collection techniques sourced from library research. The data analysis technique that the writer uses is descriptive analysis technique. From the research results it can be seen that the form of protection and management of the peat ecosystem itself has been applied through regulations issued by the government, which hint at restoring, protecting and preserving peatlands. Even so, in the process of protection and management there are factors that become obstacles and obstacles, thus the collaboration of all legal subjects, both the government and the community, is needed to support the implementation of a harmony in efforts to control forest and land fires (karhutla) itself through ecosystem protection and management. peat in West Kalimantan.